Safety of a feed additive consisting of dicopper chloride trihydroxide for all animal species (Nutreco Nederland B.V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety of a feed additive consisting of dicopper chloride trihydroxide intended for use as a nutritional additive (functional group: compounds of trace elements) for all animal species. Regarding the safety for the user, in the previous assessment, the FEEDAP Panel concluded that the additive is hazardous by inhalation, it is irritant to skin and eye and a skin and respiratory sensitiser. For the current assessment, arguments have been provided by the applicant in support of the safety of the additive for the users exposed by inhalation. The FEEDAP Panel concluded that dicopper chloride trihydroxide is irritant to skin, eyes and the respiratory system and should be considered a skin and respiratory sensitiser. Any exposure is considered a risk.